Inequality Across Space: A Sociological Imagination - Wida Ayu Puspitosari (Brawijaya Journal of Social Science, 2017)
In recent decades, the study of space has been truthfully appealing to social researchers, as it encourges them to walk through complexity of social life in which people engage to space. Space, all we know, is multiciplity dimension of the world in which we live.